Long-term rifaximin therapy as a primary prevention of hepatorenal syndrome. Issue 11 (November 2017) - Ibrahim, El-Sayed; Alsebaey, Ayman; Zaghla, Hassan; Moawad Abdelmageed, Sabry; Gameel, Khalid; Abdelsameea, Eman
Abstract : Background: Hepatorenal syndrome (HRS) is a severe complication of liver cirrhosis, with poor survival. Rifaximin is a gut-selective broad-spectrum antibiotic. Aim: The aim of this study was to evaluate the role of rifaximin as a primary prevention of HRS. Patients and methods: Eighty patients with liver cirrhosis and ascites were enrolled. They were randomized into two groups: control ( n =40) and rifaximin group ( n =40). Baseline liver function tests, renal function tests, complete blood count, international normalized ratio, urine analysis, and abdominal ultrasonography were carried out. Rifaximin 550 mg was administered twice daily for 12 weeks. Renal functions were measured every 4 weeks with monitoring of HRS occurrence and possible precipitating factor. Results: Both groups were matched for age, sex, virology, serum bilirubin, serum albumin, aspartate aminotransferase, alanine aminotransferase, hemoglobin, white blood cells, platelets, international normalized ratio, potassium, and Child–Pugh score. In contrast to the rifaximin group, the control group showed statistically significant serial blood urea nitrogen (18.84±7.17, 19.85±6.10, 21.54±4.79, and 22.96±5.82 mg/dl; P =0.001) and serum creatinine (0.94±0.25, 1.02±0.24, 1.12±0.16, and 1.21±0.17 mg/dl; P =0.001) levels. The overall blood urea nitrogen and serum creatinine change was statistically higher in the control group than the rifaximin group (20.8 vs. 18.24 mg/dl and 1.07 vs. 0.99 mg/dl, respectively). HRS developed more in the control group than the rifaximin group [9 (22.5%) vs. 2 (5%); P =0.048]. In both groups, HRS was precipitated by spontaneous bacterial peritonitis mainly and large volume paracentesis. The Child–Pugh score, control group, baseline serum sodium, and creatinine were predictors of HRS. Conclusion: Rifaximin may be useful as a primary prevention of HRS.